2015
DOI: 10.3233/wor-141898
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among middle-grade doctors of tertiary care hospital in Saudi Arabia

Abstract: The authors concluded that burnout syndrome is high among the middle-grade doctors in this medical facility and that urgent steps are needed to address this problem to ensure that these physicians remain physically and mentally healthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
2
16
2
1
Order By: Relevance
“…In addition, older physicians have lower levels of burnout [26]. Some studies have shown opposite results to the results in this study; older physicians scored a higher level of emotional exhaustion [24]. The results of this study showed that there can be some logical reasons why more experienced healthcare providers have less emotional exhaustion and depersonalization levels which is the ability to cope with stress and time management.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In addition, older physicians have lower levels of burnout [26]. Some studies have shown opposite results to the results in this study; older physicians scored a higher level of emotional exhaustion [24]. The results of this study showed that there can be some logical reasons why more experienced healthcare providers have less emotional exhaustion and depersonalization levels which is the ability to cope with stress and time management.…”
Section: Discussioncontrasting
confidence: 60%
“…On the other hand, other studies have shown that single healthcare providers score higher burnout levels than married workers [20]. In addition, studies suggest that being unmarried has a lower level of personal accomplishment and a higher level of depersonalization [24]. Evidence supports that marital status is a significant factor for burnout, and the reason behind having a high level of emotional exhaustion (EE) in married and divorced workers is the work-home stress.…”
Section: Discussionmentioning
confidence: 99%
“…Unrecognized stress and burnout were found to be associated with loss of professional enthusiasm and job satisfaction and have a psychological impact. [ 17 18 ] Emergency nurses' experience of anxiety was lower using GAD-7 when compared to EMS and ER physician which is contradictory to previous studies where anxiety symptoms exist among emergency nurses. [ 10 11 ]…”
Section: Discussionmentioning
confidence: 72%
“…Future researches is encouraged to test the effect of individual characteristics (e.g., age, family situation, years of work experience, personality, and technology acceptance/aversion) and occupational characteristics. For instance, previous research reported a significant effect of occupational characteristics [22], psychological characteristics (e.g., personality [23]), and demographic characteristics [21,61] on burnout dimensions (emotional exhaustion, depersonalization, and professional efficacy).…”
Section: Limitationsmentioning
confidence: 99%